2017
DOI: 10.1016/j.ehj.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Elevated troponin in patients with acute stroke – Is it a true heart attack?

Abstract: Although the prognostic value of a positive troponin in an acute stroke patient is still uncertain, it is a commonly encountered clinical situation given that Ischemic Heart Disease (IHD) and cerebrovascular disease (CVD) frequently co-exist in the same patient and share similar risk factors. Our objectives in this review are to (1) identify the biologic relationship between acute cerebrovascular stroke and elevated troponin levels, (2) determine the pathophysiologic differences between positive troponin in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…The long-term mortality result was also investigated in a separate study (3-year period) and the mortality was found higher in the patients with increased troponin at the time of admission. In acute stroke cases with increased troponin, both short-and long-term mortality was reported to be higher than in the group without increased troponin (11,12). Also in our study, the mortality rate was observed statistically significantly higher at the end of the third month in cases with troponin values greater than 0.028 ng/mL (p = 0.027).…”
Section: Discussionsupporting
confidence: 57%
“…The long-term mortality result was also investigated in a separate study (3-year period) and the mortality was found higher in the patients with increased troponin at the time of admission. In acute stroke cases with increased troponin, both short-and long-term mortality was reported to be higher than in the group without increased troponin (11,12). Also in our study, the mortality rate was observed statistically significantly higher at the end of the third month in cases with troponin values greater than 0.028 ng/mL (p = 0.027).…”
Section: Discussionsupporting
confidence: 57%
“…The definitions of this research were acute myocardial injury (AMI, troponin I >0.2 µg/L) (Dous et al, 2017), acute kidney injury (AKI, serum creatinine >26.5 µmol/L in 48 hours or urine volume <0.5mL/kg/h for 6 hours) (Kellum et al, 2012), respiratory failure (arterial partial oxygen pressure <60 mm Hg) (Hamp et al, 2017), digestive adverse effect (the clinical symptom of diarrhea, nausea and vomiting), low potassium (serum potassium <3.5 mmol/L) and hypoalbuminemia (serum albumin <35 g/L) (Touma and Bisharat, 2019).…”
Section: Definitionsmentioning
confidence: 99%
“…Patients with pheochromocytoma and hypertension have a 14-fold increased risk of cardiovascular events such as heart attack or stroke, with severe hypertension occurring as often as once weekly in about 75% of patients [12]. Similar to a pheochromocytoma, SAH causes an imbalance in the autonomic nervous system with a subsequent increased sympathetic output and an elevation of circulating catecholamines [13]. This tilt in normal neural homeostasis can lead to neurogenic heart syndrome, a condition where overstimulation of the sympathetic nervous system leads to cardiac arrhythmias, ultimately leading to cardiac arrest [14].…”
Section: Discussionmentioning
confidence: 99%